Qualitative analysis of a tourism area life cycle model for interacting tourism destinations - M. Rodrigo; Imène Ajala; A. K. Irhanida (Annals of Tourism Research Empirical Insights, 2023)
An extension of the tourism area life cycle (TALC) model is proposed by considering two interacting tourism destinations. Three types of interaction dynamics are investigated: competition, mutualism (or cooperation) and predator-prey. Using dynamical systems theory, aqualitative analysis of the proposed model is performed and all possible tourist equilibria are identified. These three interaction dynamics are then discussed from the perspective of nation-branding and competitive identity in the context of the race for soft power, and further illustrated empirically with examples from Malaysia and the Middle East.
Keywords: 330; Competition; Interacting tourism destinations; Mutualism; Predator-prey; Tourism area life cycle